PONCIANO TENORIO MONTES (1912-1963): PIONEER IN PSYCHIATRICS IN MICHOACAN AND FOUNDER OF THE PSYCHIATRIC HOSPITAL OF MORELIA (Tzintzun, Revista de Estudios Históricos, 2016)
This work outlines the professional life of Dr. Ponciano Tenorio Montes (1912-1963), who was the first medic with studies in psychiatrics to practice in the stateof Michoacan. Also discussed are the historic antecedents and the circumstancesthat led to the foundation in Morelia in the Medical Faculty of the first departmentof neuron-psychiatrics (1950-1952) in the country, along with the first mentalhospital in Michoacan in 1958. He was also the Regent of the First and NationalCollege of the University of Michoacan, delegate at the Fourth InternationalCongress of Mental Health in Mexico City (in December 1951) and also at the firstformal reunion of the Psychiatric Association of Latin America (APAL) in Jalapa.He is considered one of the most prominent medical doctors of his time, and becauseof this the understanding of his work contributes to the understanding of theimmediate past of medicine in Michoacan.
Keywords: Ponciano Tenorio Montes; Michoacan; Mexico; Dr. José Torres Orozco Psychiatric Hospital; Universidad Michoacana de San Nicolás de Hidalgo